Information retrieval in institutional repositories: Proposal of an ontology for Historical Organizational Memory - Estevão, Janete Saldanha Bach; Strauhs, Faimara do Rocio (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
The Historical Organizational Memory consists of the main documents that register the trajectory of an institution. The ontologies aim to make sense of the content of these repositories, using the semantic relationship of the terms that represent the area. This work establishes the basis for proposing an ontology that serves as a reference model in the field of Historical Memory Organization, promoting accurate responses from search engines and information retrieval.